O meteorito condrítico Saulo Gomes - Zanardo, Antenor [UNESP]; Navarro, Guillermo Rafael Beltram [UNESP]; Del Roveri, Carolina [UNESP]; Morales, Norberto [UNESP] (My University, 2011)
This paper aims to present the results of petrographic and lithochemical studies obtained in one of the three artifacts, which fell on the farm Buritis in Buritizal County in August 1967, which were collected and stored until the present by reporter Saulo Gomes. The petrographic analysis showed that the artifact is composed by spherical and irregular chondrules with serial granulometry and size averaging around 1 mm and the largest reaching about 6 mm in diameter. The chondrules are made of olivine, ortho and clinopyroxene, crystallite glass, nickel iron alloy and troillite (kamacite and/or taenite/tetrataenite) and inter chondrules glassy material occurs in association with troillite, nickel and other alloy iron-based compounds. The lithochemical data show excellent correlation with the C chondrite, noting only small differences above or between them. The study made it possible to classify the artifact as type L3 and L4 ordinary chondrite.

O presente texto tem o objetivo de apresentar os resultados petrográficos e litoquímicos obtidos em um dos três artefatos que caíram na fazenda Buritis, município de Buritizal, em agosto de 1967, os quais foram coletados e guardados até a presente data pelo repórter Saulo Gomes. A análise petrográfica mostrou que o artefato é constituído por côndrulos esféricos a irregulares, granulometria serial com média ao redor de 1 mm e o maior valor atingindo cerca de 6 mm de diâmetro. Os côndrulos são constituídos por olivina, orto e clinopiroxênio, vidro com cristalitos, troillita e liga ferro níquel (kamacita e/ou taenita/tetrataenita). Inter côndrulos ocorre material vítreo em associação com troillita, liga ferro níquel e outros compostos a base de ferro. Os dados litoquímicos mostram ótima correlação com o condrito C, observando-se apenas pequenas diferenças. O estudo possibilitou classificar o artefato como condrito ordinário, tipo L3 a L4.
The chondritic meteorite Saulo Gomes
Keywords: Chemical composition; Chondrite; Chondrules; City of Buritizal; Mineralogy; Petrography; chemical composition; chondrite; data set; diameter; granulometry; lithology; meteorite; mineralogy; petrography; Brazil